Creutzfeldt-Jakob Disease Presenting as Expressive Aphasia and Nonconvulsive Status Epilepticus - Hafiz B. Mahboob; Kazi H. Kaokaf; Jeremy M. Gonda (Case Reports in Critical Care)
Creutzfeldt-Jakob disease (CJD), the most common form of human prion diseases, is a fatal condition with a mortality rate reaching 85% within one year of clinical presentation. CJD is characterized by rapidly progressive neurological deterioration in combination with typical electroencephalography (EEG) and magnetic resonance imaging (MRI) findings and positive cerebrospinal spinal fluid (CSF) analysis for 14-3-3 proteins. Unfortunately, CJD can have atypical clinical and radiological presentation in approximately 10% of cases, thus making the diagnosis often challenging. We report a rare clinical presentation of sporadic CJD (sCJD) with combination of both expressive aphasia and nonconvulsive status epilepticus. This patient presented with slurred speech, confusion, myoclonus, headaches, and vertigo and succumbed to his disease within ten weeks of initial onset of his symptoms. He had a normal initial diagnostic workup, but subsequent workup initiated due to persistent clinical deterioration revealed CJD with typical MRI, EEG, and CSF findings. Other causes of rapidly progressive dementia and encephalopathy were ruled out. Though a rare condition, we recommend consideration of CJD on patients with expressive aphasia, progressive unexplained neurocognitive decline, and refractory epileptiform activity seen on EEG. Frequent reimaging (MRI, video EEGs) and CSF examination might help diagnose this fatal condition earlier.